(untitled) (Research, Society and Development, 2022)
Pregnancy is characterized as a natural, physiological and unique process experienced by women, causing biopsychosocial transformations, characterized by yearnings and expectations for the baby arrival, physical changes, and psychological changes. Alcohol consumption during the gestational period causes unsettling clinical risks for the maternal-fetal dyad. For the mother, alcohol works as an appetite suppressant, which makes an effective prenatal follow-up even more relevant, since due to this condition, a pregnant woman can suffer losses in the necessary food intake, causing non-capturing of nutrients and favoring the fetus nutritional deficiency. This protocol objective is to present steps for a scope review construction aiming to map evidences on health care for pregnant crack users. This protocol is based on Joana Briggs Institute Manual recommendations. The following databases will be used for data search: PUBMED, LILACS, SCIELO, BDEnf, Web of Science and Scopus, and CAPES Digital Library of Theses and Dissertations. Information will be collected in the extraction phase and then stored in an electronic database, created in Microsoft Excel for Windows® version 2019. This protocol inception will enable scope review methodologically based on principles established by Joanna Briggs Institute Manual and, starting from there, greater knowledge about health care for pregnant crack users.